Method for preparing SiC nanowire and ultrahigh-temperature ceramic synergistically modified carbon-based composite material in one step

Through a one-step preparation method, catalyst and silicide powder are laid on low-density C/C and high-temperature heat treatment is carried out, which solves the problems of high preparation costs, long cycles and complex processes in the prior art, and realizes SiC nanowires and ultra-high temperatures The collaborative modification of ceramics improves the performance of composite materials.

CN119409517AActive Publication Date: 2025-02-11NORTHWESTERN POLYTECHNICAL UNIV +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411572668.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-11
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

The existing toughening and toughening methods of matrix modified carbon-based composite materials are cost-effective, have long cycles and complex process flow, and the nanowires introduced first may hinder the subsequent introduction of ceramics.

Method used

采用一步制备方法,在低密度C/C上下均匀铺设催化剂和硅化物粉料,并在SPS炉中进行高温热处理,通过金刚石磨盘打磨后得到SiC纳米线增韧的碳基复合材料。

Benefits of technology

This method simplifies the process flow, shortens the preparation cycle, realizes the coordinated modification of SiC nanowires and ultra-high temperature ceramics, and improves the mechanical properties and oxidation/ablation resistance of the composite material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409517A_ABST
    Figure CN119409517A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a SiC nanowire and ultrahigh-temperature ceramic synergistically modified carbon-based composite material in one step. A certain mass of silicide powder added with a catalyst is evenly laid on the upper portion and the lower portion of low-density C / C, then the low-density C / C is placed in an SPS furnace, high-temperature heat treatment is carried out according to a set program, and then the product is obtained after surface treatment. According to the method, the SiC nanowire and ultra-high-temperature ceramic synergistic modified carbon-based composite material can be prepared through a one-step method, the SiC nanowire / particle and carbide ultra-high-temperature ceramic phase is generated in situ while infiltration is promoted through low-melting-point phase silicide, and a nano reinforcement and an anti-oxidation / ablation component can be introduced at the same time only through one step; according to the method, the mechanical property and the oxidation / ablation resistance of the carbon-based composite material can be synchronously improved, the preparation period of the method is only 1-2 hours, the experiment cost is effectively reduced, and high-flux rapid screening of modified components can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to a technology for preparing a toughened carbon-based composite material, and relates to a method for preparing a carbon-based composite material synergistically modified by SiC nanowires and ultra-high temperature ceramics in one step. Background Art

[0002] C / C composite material is a carbon-based composite material with carbon fiber as reinforcement. It is prone to oxidation and ablation damage under high-temperature aerobic conditions, which hinders the further development of the composite material. Matrix modification is one of the most effective ways to solve this problem. The introduction of ultra-high temperature ceramics into the carbon-based composite material can improve its anti-ablation performance.

[0003] Reference 1 “Shen YZ, Sun W, Xu YL, Wen QB, Zhang HB, Xiong X, Excellent oxyacetylene ablation performance of C / C-Me-Zr-Hf-C(Me=Ta,Si)compositesprepared by a novel two-step molten salt infiltration, Journal of the European Ceramic Society, 44(2024)3084-3098” used a two-step molten salt infiltration method to prepare C / C-Me-Zr-Hf(Me=Ta,Si) composites with excellent resistance to oxyacetylene ablation. The results show that the C / C-ZrHfC-SiC composites prepared by the two-step molten salt infiltration method have controllable ultra-high temperature ceramic structure and good anti-ablation performance.

[0004] Reference 2 “Dong ZJ, Yu HZ, Zhang Y, Liu B, Zhang H, Zhang JP, Fu QG, C / C-HfC-ZrC composites with excellent long-term ablation performance prepared by combining PIP and RMI, Ceramics International, 50 (2024) 13912-13923” uses a combination of polymer impregnation pyrolysis and reactive melt infiltration to prepare C / C-HfC-ZrC composites to resist long-term ablation. At a heat flux density of 4.18 MW / m 2 After ablation in oxyacetylene flame for 600s, the mass ablation rate and line ablation rate were only 0.544mg / s and 0.107μm / s.

[0005] However, ultra-high temperature ceramics are very brittle, and introducing them into carbon-based composites may reduce their mechanical properties. Nanowires, due to their special geometric structure, are a powerful tool for toughening composites. Therefore, some researchers have proposed methods such as polymer precursor conversion, chemical vapor deposition and vapor phase siliconization to introduce nanowires into carbon-based composites, which effectively improved the mechanical properties of the composites.

[0006] CN111848196B reports a method for preparing in-situ silicon carbide nanowire-toughened silicon carbide ceramics. With the help of the toughening effect of the nanowires, the cracking tendency of the silicon carbide ceramics is reduced and its thermal shock resistance is improved. However, this method requires 3 to 6 impregnation-cracking processes to densify the composite material, and the introduction of the nanowires is carried out separately from the densification process, resulting in a lengthy preparation cycle.

[0007] CN116396091 reports a method for preparing a high-strength, high-thermal-conductivity, ablation-resistant ceramic gradient-modified C / C composite material, in which a C / C composite material with a gradient distribution of SiC nanowires and ceramic components is synergistically modified is prepared. In this method, the ceramic components and SiC nanowires are introduced separately, and the preparation process is complicated. At the same time, the SiC nanowires introduced first may hinder the subsequent introduction of the ceramic components. Summary of the invention

[0008] The technical problem to be solved by the present invention is to solve the problems of high preparation cost, long cycle, complicated process flow and the possibility that the nanowires introduced first may hinder the subsequent introduction of ceramics in the existing matrix modified carbon-based composite material strengthening and toughening methods.

[0009] In view of the shortcomings of the prior art, a method for preparing SiC nanowires and ultra-high temperature ceramics synergistically modified carbon-based composites in one step is provided. A certain proportion of catalyst (including but not limited to one or more of iron and nickel metal elements and their compounds) is mixed into the silicide powder, and it is evenly laid on the low-density C / C and placed in a spark plasma sintering (SPS) mold. The installed mold is placed in an SPS furnace, and a temperature and pressure program is set for high-temperature heat treatment. After grinding with a diamond grinding disc, a carbide ultra-high temperature ceramic-SiC modified carbon-based composite toughened by SiC nanowires can be obtained.

[0010] In order to achieve the above technical purpose, the technical solution provided by the present invention is as follows:

[0011] A method for preparing a SiC nanowire and ultra-high temperature ceramic synergistically modified carbon-based composite material in one step, comprising the following steps:

[0012] S1. Low density C / C pretreatment;

[0013] S2. Preparation of silicide powder;

[0014] S3. Grind and mix the silicide powder and the catalyst evenly;

[0015] S4. The powder obtained from S3 is evenly laid on the upper and lower surfaces of the low-density C / C and placed in an SPS mold;

[0016] S5. Place the installed mold in the SPS furnace, set the program for heat treatment, and take it out after cooling;

[0017] S6. The product surface is polished and cleaned to obtain a matrix-modified carbon-based composite material toughened by SiC nanowires.

[0018] As an improvement, the preprocessing method in step S1 is:

[0019] Use deionized water to ultrasonically clean the low-density C / C, and place it in a vacuum oven at 100-120°C for 10-15 hours to ensure that the surface of the low-density C / C is dry;

[0020] As an improvement, the raw materials of the silicide powder in step S2 include: one or more of HfSi2, ZrSi2, TiSi2, TaSi2, and NbSi2 powders.

[0021] As an improvement, the preparation method of the silicide powder is:

[0022] The raw materials of the silicate powder are added into the ball mill according to the proportion and then subjected to ball milling treatment.

[0023] As an improvement, the ball milling method is:

[0024] The ball-to-material ratio is 2:1-4:1, the ball mill speed is 300-600r / min, the ball mill time is 7-12h, and then the silicide powder is placed in a vacuum oven at 100-120°C and dried for 10-15h to ensure that the powder is dry.

[0025] As an improvement, the grinding method in step S3 is to grind the silicide powder and the catalyst in an agate mortar for 15 to 35 minutes.

[0026] As an improvement, the catalyst in step S3 includes but is not limited to one or more of iron and nickel metal elements and their compounds.

[0027] As an improvement, the mass ratio of the silicide powder to the catalyst in step S3 is 300:1 to 500:1.

[0028] As an improvement, the pressure procedure in step S5 is to apply a pressure of 6 to 8 kN throughout the entire process.

[0029] As an improvement, the temperature program in step S5 is:

[0030] Heat to 1500-1900°C in a vacuum environment, with a heating rate of 400-500°C / min below 1500°C and a heating rate of 100-200°C / min above 1500°C, keep warm for 30-90 minutes, and then cool to room temperature at a cooling rate of 100-200°C / min.

[0031] As an improvement, the method of the polishing and cleaning step in step S6 is:

[0032] Use a 320-500 mesh diamond grinding wheel to grind and clean the graphite paper remaining on the sample surface.

[0033] The present invention proposes a one-step method for preparing SiC nanowires and ultra-high temperature ceramics synergistically modified carbon-based composite materials, a certain mass of silicide powder with added catalyst (including but not limited to one or more of iron and nickel metal elements and their compounds) is evenly laid on the low-density C / C, and placed in an SPS mold. The installed mold is placed in an SPS furnace, and the temperature and pressure program is set for high-temperature heat treatment. After grinding with a diamond grinding disc, a matrix-modified carbon-based composite material toughened by SiC nanowires can be obtained. Existing methods for toughening matrix-modified carbon-based composite materials with nanowires, such as polymer precursor conversion method, chemical vapor deposition method and gas phase siliconization method, have the disadvantages of high preparation cost, long cycle, and complex process flow. In addition, the nanowires introduced first are easy to block pores, affecting the introduction of subsequent ceramics. This method gives full play to the advantages of SPS equipment, and greatly shortens the preparation cycle of nanowire toughening and matrix modification integration. This method has simple operation steps and short preparation cycle, and is suitable for the rapid and low-cost preparation of SiC nanowire-toughened carbon-based / ceramic-based composite materials.

[0034] The present invention has the advantages that:

[0035] 1. This method can prepare SiC nanowire-toughened modified carbon-based composites in one step. SiC nanowires / particles and carbide ultra-high temperature ceramics are generated in situ while silicides play a role in promoting melt infiltration. The simultaneous introduction of SiC nanowires, SiC particles, and carbide ceramic phases can be completed in just one step, solving the problem of pore clogging caused by the introduction of nanowires / ceramic phases first, which hinders the introduction of subsequent ceramic phases.

[0036] 2. This method simultaneously obtains SiC nanowires and multi-element ultra-high temperature ceramic phases through in-situ reaction between silicide and pyrolytic carbon inside carbon-based composite materials. On the one hand, the in-situ synthesized nanowires can achieve micro-nano multi-scale toughening of carbon-based composite materials and ultra-high temperature ceramic phases, improving the mechanical properties of the composite materials. On the other hand, the introduction of multi-element ultra-high temperature ceramic phases can effectively improve the antioxidant / ablation properties of the composite materials.

[0037] 3. This method promotes the diffusion of silicides into the interior of low-density C / C by pressurizing. The preparation cycle only takes 1 to 2 hours, which can achieve high-throughput rapid screening of modified components. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is the XRD spectrum of the SiC nanowire-toughened (Zr, Hf)C-SiC-C / C composite material in Example 1.

[0039] Figure 2 This is a cross-sectional SEM photograph of the SiC nanowire-toughened (Zr, Hf)C-SiC-C / C composite material in Example 1.

[0040] Figure 3 This is the XRD spectrum of the SiC nanowire-toughened (Zr, Hf)C-SiC-C / C composite material in Example 2.

[0041] Figure 4 This is a cross-sectional SEM photograph of the SiC nanowire-toughened (Zr, Hf)C-SiC-C / C composite material in Example 3. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.

[0043] Example 1

[0044] This embodiment discloses a method for preparing a carbon-based composite material synergistically modified by SiC nanowires and ultra-high temperature ceramics in one step, comprising the following steps:

[0045] S1. Low-density C / C pretreatment

[0046] Ultrasonic cleaning with deionized water, the size is Φ29mm×6mm, the density is 1.12g / cm 3 The low-density C / C was placed in a vacuum oven at 100°C for 12 hours.

[0047] S2. Preparation of Silicide Powder

[0048] Pour ZrSi2 and HfSi2 in a molar ratio of 1:1 into a ball mill and use a ball mill to mill them. Add an appropriate amount of penetration enhancer, the ball-to-material ratio is 2:1, the ball mill speed is 350r / min, and after ball milling for 7 hours, place the silicate powder in a vacuum oven at 120°C and dry it for 12 hours.

[0049] S3. Grind and mix the silicide powder and catalyst evenly

[0050] The silicate powder and nickel powder were ground in an agate mortar at a mass ratio of 360:1 for 20 min.

[0051] S4. Evenly spread 4.01g of mixed powder with nickel powder on the upper and lower surfaces of the low-density C / C, and place it above the lower punch of the SPS mold. Wrap the low-density C / C and the powder with graphite paper, place a Φ30mm graphite paper in the area where the powder contacts the upper and lower punches, and finally press the upper punch in.

[0052] S5. Place the installed mold in an SPS furnace, set the pressure to 7 kN, heat to 1500°C at a heating rate of 450°C / min under vacuum, continue to heat to 1700°C at a heating rate of 200°C / min, keep warm for 30 minutes, cool to room temperature at a cooling rate of 200°C / min and take out.

[0053] S6. Use a 325-mesh diamond grinding wheel to polish and clean the graphite paper remaining on the sample surface to obtain SiC nanowire-reinforced (Zr,Hf)C-SiC modified C / C composite materials.

[0054] Its XRD Figure 1 As shown in the figure, it can be seen that there are only carbon peaks, β-SiC and (Zr,Hf)C peaks in the sample, and no impurity phase. Its microstructure is as follows Figure 2 As shown, the sample has a high content of nanowires, the ceramic phase is tightly wrapped around the carbon fibers, and the nanowires are radially arranged around the ceramic phase.

[0055] Example 2

[0056] This embodiment discloses a method for preparing a carbon-based composite material synergistically modified by SiC nanowires and ultra-high temperature ceramics in one step, comprising the following steps:

[0057] S1. Low-density C / C pretreatment

[0058] Ultrasonic cleaning with deionized water, the size is Φ29mm×6mm, the density is 1.19g / cm 3 The low-density C / C was placed in a vacuum oven at 100°C for 12 hours.

[0059] S2. Preparation of Silicide Powder

[0060] Pour ZrSi2 and HfSi2 in a molar ratio of 1:1 into a ball mill and use a ball mill for ball milling. The ball-to-material ratio is 2:1 and the ball milling speed is 400r / min. After ball milling for 8 hours, place the silicide powder in a vacuum oven at 120°C and dry it for 12 hours.

[0061] S3. Grind and mix the silicide powder and catalyst evenly

[0062] The silicate powder and ferrous sulfate were ground in an agate mortar at a mass ratio of 500:1 for 30 minutes.

[0063] S4. Evenly spread 4.74g of mixed powder with ferrous sulfate on the upper and lower surfaces of the low-density C / C, and place it above the lower punch of the SPS mold. Wrap the low-density C / C and the powder with graphite paper, place a Φ30mm graphite paper in the area where the powder contacts the upper and lower punches, and finally press in the upper punch.

[0064] S5. Place the installed mold in an SPS furnace, set the pressure to 8 kN, heat to 1500°C at a heating rate of 450°C / min in a vacuum environment, continue to heat to 1700°C at a heating rate of 200°C / min, keep warm for 40 minutes, cool to room temperature at a cooling rate of 200°C / min and take out.

[0065] S6. Use a 320-mesh diamond grinding wheel to polish and clean the graphite paper remaining on the sample surface to obtain SiC nanowire-reinforced (Zr,Hf)C-SiC modified C / C composite materials.

[0066] The XRD pattern of the product in this example is as follows: Figure 3 As shown, the sample only has carbon peaks, β-SiC and (Zr,Hf)C peaks, and no impurity phase.

[0067] Example 3

[0068] This embodiment discloses a method for preparing a carbon-based composite material synergistically modified by SiC nanowires and ultra-high temperature ceramics in one step, comprising the following steps:

[0069] S1. Low-density C / C pretreatment

[0070] Ultrasonic cleaning with deionized water, the size is Φ29mm×6mm, the density is 1.24g / cm 3 The low-density C / C was placed in a vacuum oven at 100°C for 12 hours.

[0071] S2. Preparation of Silicide Powder

[0072] Pour ZrSi2 and HfSi2 in a molar ratio of 2:1 into a ball mill and use a ball mill for ball milling. The ball-to-material ratio is 2:1 and the ball milling speed is 300r / min. After ball milling for 8 hours, place the silicide powder in a vacuum oven at 120°C and dry it for 12 hours.

[0073] S3. Grind and mix the silicide powder and catalyst evenly

[0074] The silicide powder and nickel powder were ground in an agate mortar at a mass ratio of 400:1 for 25 min.

[0075] S4. Evenly spread 2.37g of mixed powder with nickel powder on the upper and lower surfaces of the low-density C / C, and place it above the lower punch of the SPS mold. Wrap the low-density C / C and the powder with graphite paper, place a Φ30mm graphite paper in the area where the powder contacts the upper and lower punches, and finally press in the upper punch.

[0076] S5. Place the installed mold in an SPS furnace, set the pressure to 7.5 kN, heat to 1500°C at a heating rate of 450°C / min in a vacuum environment, continue to heat to 1750°C at a heating rate of 200°C / min, keep warm for 30 minutes, cool to room temperature at a cooling rate of 200°C / min and take out.

[0077] S6. Use a 320-mesh diamond grinding wheel to polish and clean the graphite paper remaining on the sample surface to obtain SiC nanowire-reinforced (Zr,Hf)C-SiC modified C / C composite materials.

[0078] The microstructure of the product in this embodiment is as follows Figure 4 As shown, the ceramic phase is tightly wrapped around the carbon fibers, and the nanowires grow between the ceramic phases.

[0079] Example 4

[0080] This embodiment discloses a method for preparing a carbon-based composite material synergistically modified by SiC nanowires and ultra-high temperature ceramics in one step, comprising the following steps:

[0081] S1. Low-density C / C pretreatment

[0082] Ultrasonic cleaning with deionized water, the size is Φ29mm×6mm, the density is 1.24g / cm 3 The low-density C / C was placed in a vacuum oven at 110°C for 10 hours.

[0083] S2. Preparation of Silicide Powder

[0084] TiSi2 and TaSi2 were poured into a ball mill at a molar ratio of 2:1 and ball milled using a ball mill. The ball-to-material ratio was 4:1 and the ball mill speed was 600 r / min. After ball milling for 10 hours, the silicate powder was placed in a vacuum oven at 120°C and dried for 12 hours.

[0085] S3. Grind and mix the silicide powder and catalyst evenly

[0086] The silicide powder and nickel powder were ground in an agate mortar at a mass ratio of 300:1 for 15 min.

[0087] S4. Evenly spread 2.37g of mixed powder with nickel powder on the upper and lower surfaces of the low-density C / C, and place it above the lower punch of the SPS mold. Wrap the low-density C / C and the powder with graphite paper, place a Φ30mm graphite paper in the area where the powder contacts the upper and lower punches, and finally press in the upper punch.

[0088] S5. Place the installed mold in an SPS furnace, set the pressure to 6 kN, heat to 1500°C at a heating rate of 400°C / min in a vacuum environment, continue to heat to 1800°C at a heating rate of 100°C / min, keep warm for 30 minutes, cool to room temperature at a cooling rate of 100°C / min and take out.

[0089] S6. Use a 400-mesh diamond grinding wheel to polish and clean the graphite paper remaining on the sample surface to obtain SiC nanowire-reinforced (Ti, Ta) C-SiC modified C / C composite materials.

[0090] Example 5

[0091] This embodiment discloses a method for preparing a carbon-based composite material synergistically modified by SiC nanowires and ultra-high temperature ceramics in one step, comprising the following steps:

[0092] S1. Low-density C / C pretreatment

[0093] Ultrasonic cleaning with deionized water, the size is Φ29mm×6mm, the density is 1.24g / cm 3 The low-density C / C was placed in a vacuum oven at 120°C and dried for 10 hours.

[0094] S2. Preparation of Silicide Powder

[0095] Pour TiSi2 and NbSi2 in a molar ratio of 2:1 into a ball mill and use a ball mill for ball milling. The ball-to-material ratio is 2:1 and the ball milling speed is 500r / min. After ball milling for 12 hours, place the silicide powder in a vacuum oven at 120°C and dry it for 15 hours.

[0096] S3. Grind and mix the silicide powder and catalyst evenly

[0097] The silicide powder and nickel powder were ground in an agate mortar at a mass ratio of 500:1 for 35 minutes.

[0098] S4. Evenly spread 2.37g of mixed powder with nickel powder on the upper and lower surfaces of the low-density C / C, and place it above the lower punch of the SPS mold. Wrap the low-density C / C and the powder with graphite paper, place a Φ30mm graphite paper in the area where the powder contacts the upper and lower punches, and finally press in the upper punch.

[0099] S5. Place the installed mold in an SPS furnace, set the pressure to 8 kN, heat to 1500°C at a heating rate of 500°C / min in a vacuum environment, continue to heat to 1900°C at a heating rate of 100°C / min, keep warm for 30 minutes, cool to room temperature at a cooling rate of 150°C / min and take out.

[0100] S6. Use a 500-mesh diamond grinding wheel to polish and clean the graphite paper remaining on the sample surface to obtain SiC nanowire-reinforced (Ti, Nb)C-SiC modified C / C composite materials.

[0101] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing SiC nanowires and ultra-high temperature ceramics synergistically modified carbon-based composite materials in one step, characterized in that: The steps include: S1. Low density C / C pretreatment; S2. Preparation of silicide powder; S3. Grind and mix the silicide powder and the catalyst evenly; S4. The powder obtained from S3 is evenly laid on the upper and lower surfaces of the low-density C / C and placed in an SPS mold; S5. Place the installed mold in the SPS furnace, set the program for heat treatment, and take it out after cooling; S6. The product surface is polished and cleaned to obtain a matrix-modified carbon-based composite material toughened by SiC nanowires.

2. The method for preparing SiC nanowire and ultra-high temperature ceramic synergistically modified carbon-based composite materials in one step according to claim 1, characterized in that: The pretreatment method in step S1 is: Use deionized water to ultrasonically clean the low-density C / C, and place it in a vacuum oven at 100-120°C for 10-15 hours to ensure that the surface of the low-density C / C is dry.

3. The method for preparing SiC nanowire and ultra-high temperature ceramic synergistically modified carbon-based composite materials in one step according to claim 1, characterized in that: The raw materials of the silicide powder in step S2 include: one or more of HfSi2, ZrSi2, TiSi2, TaSi2, and NbSi2 powders.

4. The method for preparing SiC nanowire and ultra-high temperature ceramic modified carbon-based composite material in one step according to claim 3, characterized in that: The preparation method of the silicide powder is: The raw materials of the silicate powder are added into the ball mill according to the proportion and then subjected to ball milling treatment.

5. The method for preparing SiC nanowire and ultra-high temperature ceramic synergistically modified carbon-based composite materials in one step according to claim 4, characterized in that: The method of the ball milling treatment is: The ball-to-material ratio is 2:1-4:1, the ball mill speed is 300-600r / min, the ball mill time is 7-12h, and then the silicide powder is placed in a vacuum oven at 100-120°C and dried for 10-15h to ensure that the powder is dry.

6. The method for preparing SiC nanowire and ultra-high temperature ceramic synergistically modified carbon-based composite material in one step according to claim 1, characterized in that: The grinding method in step S3 is: Grind the silicide powder and catalyst in an agate mortar for 15 to 35 minutes; In step S3, the mass ratio of the silicide powder to the catalyst is 300:1 to 500:

1.

7. The method for preparing SiC nanowire and ultra-high temperature ceramic synergistically modified carbon-based composite materials in one step according to claim 1, characterized in that: The catalyst in step S3 includes, but is not limited to, one or more of iron and nickel metal elements and their compounds.

8. The method for preparing SiC nanowire and ultra-high temperature ceramic synergistically modified carbon-based composite materials in one step according to claim 1, characterized in that: The pressure program in step S5 is to apply a pressure of 6 to 8 kN throughout the entire process.

9. The method for preparing SiC nanowire and ultra-high temperature ceramic synergistically modified carbon-based composite material in one step according to claim 1, characterized in that: The temperature program in step S5 is: Heat to 1500-1900°C in a vacuum environment, with a heating rate of 400-500°C / min below 1500°C and a heating rate of 100-200°C / min above 1500°C, keep warm for 30-90 minutes, and then cool to room temperature at a cooling rate of 100-200°C / min.

10. The method for preparing SiC nanowire and ultra-high temperature ceramic synergistically modified carbon-based composite material in one step according to claim 1, characterized in that: The method of the polishing and cleaning step in step S6 is: The graphite paper remaining on the sample surface was polished and cleaned using a 320-500 mesh diamond grinding wheel.

Citation Information

Patent Citations

  • A method for preparing in-situ silicon carbide nanowire-toughened silicon carbide ceramics

    CN111848196B

  • Preparation method of nanobelt toughened silicon-based ceramic coating

    CN102718527A

  • Preparation method for thin wall or tapered member made from one-dimensional nanofiber reinforced and toughened carbon-ceramic composite

    CN103964883A

  • Preparation method of ultra-long SiC nanowires

    CN104773735A

  • Preparation method of SiC nano-wire and SiC-MoSi2-CrSi2 coating co-growth composite

    CN106588121A